Functional outcome following open reduction and internal fixation of proximal humerus fractures with locking compression plate - M., Mohamed Nishad; Shakeeb K. U., Mohamed; A. J., Gijo (International Journal of Research in Orthopaedics, 2020)
Background: Proximal humerus fractures (PHFs) are common upper extremity fractures representing break in humerus bone. Incidences of PHFs increased in last few years due to life style changes and increased road accidents. Appropriate management strategy for PHFs is still uncertain. The aim of current study is to assess the functional outcome following open reduction and internal fixation of proximal humerus fractures using locking compression plates. Methods: Current study is a descriptive investigation conducted on 31 PHFs patients admitted to baby memorial hospital, calicut, between January 2013 to June 2014. Surgical management of PHFs was done by open reduction and internal fixation using locking compression plates and functional outcomes and complications of the employed treatment modality were investigated. Results: PHFs were observed to be common in 41-60 years age group, with 65% males being affected. Road accidents and domestic falls were observed to be the most common causes of PHFs in younger and elderly populations respectively. Three parts PHFs were observed to be more prevalent, followed by two and four parts fractures. Results of current study revealed that majority of PHFs united by 8-10 weeks duration with 22.58% cases with excellent and 41.93%, 16.12% and 19.35% cases with good, moderate and poor constant and Murley score respectively. Two patients reported post-operative complication of shoulder stiffness, while one patient each reported plate impingement, varus maluion, infection and varus malunion with intraarticular screw cut-out. Conclusions: Locking compression plates (PHILOS/PHLP) is an efficient treatment modality for proximal humerus fractures allowing early mobilization and good functional outcome.